Predictors for Transcultural Self-efficacy of Nursing Students: Application of Ecological Model - Asurakkody, T.A. (My University, 2019)
Objective: This research aimed to explore the significant factors for transcultural self-efficacy applying the Bronfenbrenner's ecological framework. Objectives were to identify the degrees of three domains; cognitive, practical and affective of transcultural self-efficacy, to find the significant differences between demographic factors and transcultural self-efficacy, to examine the relationship among variables and to explore the predictors for the transcultural self-efficacy of nursing students according to the levels of the ecological model. Methods: This was a cross-sectional, quantitative correlational design with secondary data analysis using hierarchical regression models. Results: Demographic factors; geographic location, age, gender and relationship with multicultural groups were significantly associated with transcultural self-efficacy. Geographic location, cultural sensitivity, interpersonal communication skills, and emotional regulation were the predictors for transcultural self-efficacy. Conclusion: Based on the findings, macro and microsystem, and ontogenic factors emphasize the needs of developing knowledge, skills and most importantly attitudes towards the social justice, interacting with every people with no bias on their race, religion, social status controlling their self-emotions and being empathy in nursing students.
Keywords: Transcultural nursing; Self-efficacy; Education